ENTERPRISE ARCHITECTURE PLANNING AS A BLUE PRINT PROMOTION STRATEGY FOR MAHAN TAPIS' BUSINESS MANAGEMENT GROUP - Agus Salim; Muhamad Muslihudin; Fauzi Fauzi (LPPM STMIK Pringsewu, 2023)
The advances and technological developments that we enjoy today are the result of the era of globalization. The existence of technological advances in the business world is marked by the emergence and increase of Micro, Small, and Medium Enterprises (MSMEs). The problems that occur in the scope of business actors show that business actors in Pringsewu Regency still depend on simple customer-to-customer (C2C) business management. Research conducted by designing Enterprise Architecture Planning for this group of business actors is expected to be able to encourage business progress and business quality, such as changes in promotion strategies and sales transactions. Enterprise Architecture Planning (EAP) is a modern approach to planning data quality and achieving information system missions, including the steps taken to define the architecture for using information to support business and plan the implementation of that architecture. The results of the research are in the form of system architecture design, interface architecture design, and technology architecture design. The resulting architectural design allows for more open coordination between IT and business units, providing businesses with opportunities to prioritize investments and making it easy to test the current architecture against long-term goals.